2017
DOI: 10.4103/ijem.ijem_20_17
|View full text |Cite
|
Sign up to set email alerts
|

Gemigliptin: Newer promising gliptin for type 2 diabetes mellitus

Abstract: The dipeptidyl peptidase-4 (DPP-4) inhibitors have facilitated the management of type 2 diabetes mellitus (T2DM) owing to their superior efficacy and safety with low incidence of adverse effects. Gemigliptin is a new member of this family of drugs, and studies have revealed certain advantages of gemigliptin use compared to its previous congeners. Besides, this drug has also been studied for the treatment of T2DM as monotherapy, in combination with metformin or other oral antidiabetic drugs and in T2DM with mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Gemigliptin is an oral anti-hyperglycemic agent (anti-diabetic drug) of the new DPP4 inhibitor class of drugs approved in global markets [ 11 12 ]. However, it has not been investigated whether gemigliptin directly affect EDR in disease models as well as in normal control.…”
Section: Introductionmentioning
confidence: 99%
“…Gemigliptin is an oral anti-hyperglycemic agent (anti-diabetic drug) of the new DPP4 inhibitor class of drugs approved in global markets [ 11 12 ]. However, it has not been investigated whether gemigliptin directly affect EDR in disease models as well as in normal control.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, in terms of metabolism of DDP-4 inhibitors, saxagliptin and gemigliptin are metabolized by CYP3A4 and therefore can be used with immunosuppressive agents. All gliptins are excreted predominantly by the kidney as an unchanged parent compound, excluding linagliptin and gemigliptin, which are excreted mainly by biliary excretion and therefore, do not need renal dose adjustment [ 60 , 61 ].…”
Section: Antidiabetic Agentsmentioning
confidence: 99%
“…2 Gemigliptin is a potent DPP-4 inhibitor that has been approved for use in patients with type 2 diabetes, and it has pleiotropic effects in addition to its glucose-lowering effect, including inhibition of lipopolysaccharide (LPS)-induced proin ammatory effects in vascular endothelial cells by attenuating NF-kappa B and c-Jun NH (2)-terminal kinase (JNK) signaling via an AMP-activated protein kinase (AMPK)-dependent mechanism. 3 A recent study found that gemigliptin attenuated the calci cation of the abdominal aorta as well as RUNX2 and phosphate-induced Pit-1 mRNA expression, and reactive oxygen species formation. Therefore, gemigliptin could bene t vascular calci cation in patients with a high risk of disease, especially diabetic nephropathy.…”
Section: Introductionmentioning
confidence: 99%